A disease‐associated mutation in the adhesion GPCR BAI2 (ADGRB2) increases receptor signaling activity. Issue 12 (20th September 2017) - Purcell, Ryan H.; Toro, Camilo; Gahl, William A.; Hall, Randy A.
Abstract: Mutations in G protein‐coupled receptors (GPCRs) that increase constitutive signaling activity can cause human disease. A de novo C‐terminal mutation (R1465W) in the adhesion GPCR BAI2 (also known as ADGRB2 ) was identified in a patient suffering from progressive spastic paraparesis and other neurological symptoms. In vitro studies revealed that this mutation strongly increases the constitutive signaling activity of an N‐terminally cleaved form of BAI2, which represents the activated form of the receptor. Further studies dissecting the mechanism(s) underling this effect revealed that wild‐type BAI2 primarily couples to Gαz, with the R1465W mutation conferring increased coupling to Gαi . The R1465W mutation also increases the total and surface expression of BAI2. The mutation has no effect on receptor binding to β‐arrestins, but does perturb binding to the endocytic protein endophilin A1, identified here as a novel interacting partner for BAI2. These studies provide new insights into the signaling capabilities of the adhesion GPCR BAI2/ ADGRB2 and shed light on how an apparent gain‐of‐function mutation to the receptor's C‐terminus may lead to human disease. Abstract : BAI2 signaling model: shedding of the N terminus results in a constitutively active BAI2 (BAI2ΔNT). The receptor couples to Gαz, which liberates Gβγ subunits and leads to calcium influx. The disease‐associated R1465W mutation in BAI2ΔNT results in higher levels of receptor surface expression, additional coupling to Gαi and decreased interaction with endophilin A1 (EndoA1).